Analisis Kebijakan Kota Layak Anak Dalam Perspektif Hak Sipil Dan Kebebasan Anak Di Kota Surabaya - Catur Ajeng Kartika Ria; Yusuf Hariyoko; Muhammad Roisul Basyar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Children are the future leaders of a nation's development, thus they have the right to special treatment in the form of protection and child rights. Accelerating the Convention on the Rights of the Child, the Child-Friendly City (CFC) policy was initiated in 2006. In its implementation, CFC is divided into 5 clusters of children's rights that must be fulfilled, one of which is civil rights and freedoms. Surabaya City is recognized as a Child-Friendly City and has maintained this status for the past six years. Given this achievement, it is interesting to analyze the implementation of the CFC in Surabaya concerning the cluster of Civil Rights and Freedoms. This study employs a descriptive qualitative research method, gathering both primary and secondary data, which are comprehensively analyzed through data reduction, presentation, and conclusion drawing. The research findings reveal strong commitment demonstrated by Surabaya City in its Child-Friendly City policy to fulfill children's civil rights and freedoms, evidenced by easy access to birth certificates and identity cards for children, as well as the establishment of the Child Friendly Information Center (Pusat Informasi Sahabat Anak - PISA) enabling children to access information and exchange ideas freely. There is a need for enhanced collaboration among government, NGOs, and the community to ensure the equitable implementation of the Child-Friendly City initiative, extending to suburban areas. Keywords: Public Policy, Child-Friendly City, Children's Civil Rights and Freedoms